The Influence of Strategic Alliance On Cibinong Science and Technology Park (C-STP) Performance - Hidayat, Anang; Hendrix, Tommy; Putri, V. Susirani Kusuma (School of Business and Management Institut Teknologi Bandung, 2016)
Abstract. Science and Technology Parks (STPs) have generated a thriving debate among academics, practitioners and policy makers on their effectiveness as instruments of innovation policy. Meanwhile, the relationship between factors including the actors involved in the implementation of STP became an obstacle. The strategic alliance is one of the management approaches that can be used to answer the question. The purpose of this study was to analyze the impact of the implementation of the strategic alliance and its influence on the performance of C-STP, and examines the relationship between organizations resource availability and absorptive capacity as well as type of alliances with organizational performance. Collecting data in this study using a questionnaire with 32 respondents were then analyzed using Structural Equation Modeling (SEM). The results show that collaboration and partnership is a factor to be considered to enhance the capabilities and performance of C-STP. Meanwhile, C-STP need to increase their efforts in improving internal resources is a source of competitive advantage in order to achieve superior business performance.Keyword: Absorptive capacity, C-STP, resources, strategic alliance, structural equation modeling